Efektivitas Model Problem Based Learning dalam Meningkatkan Kemandirian dan Hasil Belajar pada Pembelajaran Matematika: Studi pada siswa Kelas IVB SD Negeri 16 Pontianak Timur - Rizka Aspriliana; Yulis Jamiah; Dede Suratman; Agung Hartoyo; Bistari (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
The purpose of this study describes the effectiveness of the Problem Based Learning model in increasing learning independence and learning outcomes of grade IV students in mathematics learning in elementary schools. The research method used is an experimental method with quasi-experimental design, the form of one group pretest – posttest design. Data collection tools in the form of observation sheets for the implementation of the Problem Based Learning model, learning independence questionnaires and student learning outcomes test sheets in the form of essays totaling 10 questions. Based on the results of the study, the average implementation of the learning model in the very good category was 90% at the first meeting and 95% at the second meeting. The Problem Based Learning model is effective in increasing learning independence and student learning outcomes as evidenced by the results of hypothesis tests obtained by the variables of learning independence and learning outcomes based on GIS (2-tailed) is 0.000 < 0.05. The variables of learning independence and learning outcomes obtained a significance value of 0.000 which is smaller than the significance of 0.005. Based on statistical calculations, the average learning outcomes of students before treatment was 62.39 and the average learning outcomes of students after treatment were 77.75. This means that the use of the Problem Based Learning model is effective in increasing learning independence, and the learning outcomes of grade IV students in mathematics learning in elementary schools.